Universalisation of liberal democracy, American exceptionalism and racism - Cuadro, Mariela (2011)
The hegemonic idea of liberal democracy was one of the axes of the most recent interventionist policies of the United States and has its roots in American exceptionalism, understood as a fervent nationalism. Indeed, an idea of superiority underlies it. The paper affirms that it becomes a form of racism that we will label cultural racism utilizing the toolbox of Foucauldian thinking.